Regional body composition determined by dual-energy X-ray absorptiometry. Relation to training, sex hormones, and serum lipids in male long-distance runners - Hetland, M. L.; Haarbo, J.; Christiansen, C. (Scandinavian Journal of Medicine & Science in Sports, 1998)
This study investigated the regional distribution of fatty and lean tissue in long-distance runners, and the relation to training, sex hormones, and serum lipids. One hundred and twenty lean men (22 elite, 86 recreational runners and 12 non-running controls) aged 32 +/- 8.1 years (mean +/- SD) participated. Body composition (adipose and lean tissue) was measured by dual-energy x-ray absorptiometry in the total body and in the abdomen, the arms and the legs. Regional and total body fat correlated inversely with the performance at an incremental treadmill exercise test (-0.61 < r < -0.52, P < 0.0001), and the fat percentage in the abdomen and in the legs was 42% and 36% lower in the elite runners in comparison with the non-running controls. Sex hormonal status and serum lipids were unrelated to training. After multiple regression analysis the most significant determinant of the fat percentage in the legs was the weekly distance run (partial r = -0.40, P < 0.0001), whereas in the abdominal region the free testosterone index also contributed strongly (partial r = 0.39, P < 0.0001). In conclusion, long-distance runners had very low amounts of fatty tissue in the abdomen and in the extremities, and the fat percentages in the abdomen and in the legs were associated with both the training intensity and androgenic activity. Since the abdominal fatty tissue is a significant risk factor for cardiovascular disease, running may have a positive impact on the long-term risk.